Dynamics of salivary cortisol in chronic kidney disease patients at stages 1 through 4 - Cardoso, Estela M. del Luján (2016)
Context: End-stage renal disease has been associated with derangement of the HPA function. The dynamics of this axis in early stages of renal disease (CKD) has not been assessed. Objectives: To evaluate in patients with CKD at stages 1–4 (KDOQI): the diurnal variation of salivary cortisol; the suppressibility of cortisol in saliva and serum after an overnight oral 1 mg dexamethasone suppression test (1 mg DST) with simultaneous measurement of circulating dexamethasone. Design and Methods: 80 CKD outpatients and 40 healthy subjects were included. All CKD collected whole saliva at 08·00 and 23·00 h (SAF23) on two nonconsecutive days. Thereafter at 08·00 h, following 1 mg DST, saliva and blood were obtained. Salivary and serum cortisol as well as CBG were assessed by RIA, dexamethasone by ELISA and serum free cortisol was calculated. Results: SAF23 correlated negatively with glomerular filtration rate (GFR). The fraction of free cortisol in serum and saliva after 1 mg DST, correlated positively and significantly in both patients with CKD and healthy subjects (r: 0·86 and r: 0·85, respectively; P < 0·0001 for both). Ten percent of CKD with GFR < 90 ml/min/1·73 m2 had false positive results unrelated to dexamethasone and CBG concentrations. Conclusions: False positive responses to 1 mg DST were associated with GFR < 90 ml/min/1·73 m2. This could not be ascribed to either defects in dexamethasone absorption or CBG concentrations. Higher dexamethasone doses were necessary to achieve adequate HPA suppression. Salivary cortisol was useful to assess circadian cortisol levels and feed-back regulation in CKD.